Ethical Decision Making and the Employed Lawyer - Gunz, Sally (Journal of business ethics, 2007)
This article addresses one of the more disturbing questions raised by the major financial failures of the recent past; namely, how it could be that professionals, highly trained both in ethics and technical disciplines, should apparently collude with management in corporate misbehaviour. The article builds on evidence suggesting that professionals in employment contexts find ways of adapting in order to minimise perceived or actual conflict between their professional and organizational obligations and that this, in turn, may affect the way in which they exercise professional judgment. It uses identity theory to propose that professionals may adopt modified identities when employed and that these identities may be expressed, in part, in the way in which they resolve ethical dilemmas. The article reports on the results of a qualitative study in which corporate counsel showed evidence of adopting these identities. The findings suggest that this line of research offers insight into a far more complex world of employed professionals than that traditionally hypothesised and that the popular approach of regulators and others to monitoring corporate governance by appointing professionals as gate-keepers within the organization is perhaps problematic.